2011
DOI: 10.1093/eurheartj/ehr111
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged overcirculation-induced pulmonary arterial hypertension as a cause of right ventricular failure

Abstract: Prolonged left-to-right shunting in piglets does not further aggravate pulmonary vasculopathy, but is a cause of RV failure, which appears related to an activation of apoptosis and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 51 publications
11
67
0
Order By: Relevance
“…This is in line with reports that the chronically volume-overloaded RV cannot increase contractility in response to acute pressure overload (46). Studies in large animal models of combined volume and pressure overload have shown that during disease progression contractility initially increases, but falls back to pseudonormal levels in a more advanced stage of RV dysfunction (28,40,41). Causal factors for the blunted contractility response may include loss of peristaltic contraction pattern (33), disturbed calcium homeostasis (8,26), and changes in coronary perfusion (46).…”
Section: Additional Volume Overload In Ph Blunts the Contractility Resupporting
confidence: 85%
“…This is in line with reports that the chronically volume-overloaded RV cannot increase contractility in response to acute pressure overload (46). Studies in large animal models of combined volume and pressure overload have shown that during disease progression contractility initially increases, but falls back to pseudonormal levels in a more advanced stage of RV dysfunction (28,40,41). Causal factors for the blunted contractility response may include loss of peristaltic contraction pattern (33), disturbed calcium homeostasis (8,26), and changes in coronary perfusion (46).…”
Section: Additional Volume Overload In Ph Blunts the Contractility Resupporting
confidence: 85%
“…3 The current understanding of the pathophysiology of RV failure involves neurohumoral activation, expression of inflammatory mediators, apoptosis, capillary loss, oxidative stress, and metabolic shifts, with variable fibrosis and hypertrophy. 3,42 The exact sequence of events and interactions is being explored, and each has still to be referred to sound measurements of function, as illustrated in recent studies that showed inflammation and apoptosis to be correlated with decreased E max /E a in acute 43 as well as chronic 25,44 models of RV failure as a universal relationship ( Figure 5). …”
Section: Coupling Of Systolic Function To Afterloadmentioning
confidence: 99%
“…In fact, only recently has consideration been given to RV function within the context of the larger lung-pulmonary circulatory-RV apparatus. 5,9 This is a critical distinction, however, because defining the right heart axis in this way reidentifies the RV as a specific participant in the pathobiology of pulmonary hypertension and potential therapeutic target per se, thereby parting from traditional dogma in which RV dysfunction is a consequence of pulmonary vascular disease, an indicator of irreversible cardiac injury, and a dismal prognostic marker.…”
Section: Article See P 2859mentioning
confidence: 99%
“…In fact, only recently has consideration been given to RV function within the context of the larger lung-pulmonary circulatory-RV apparatus. 5,9 This is a critical distinction, however, because defining the right heart axis in this way reidentifies the RV as a specific participant in the pathobiology of pulmonary hypertension and potential therapeutic target per se, thereby parting from traditional dogma in which RV dysfunction is a consequence of pulmonary vascular disease, an indicator of irreversible cardiac injury, and a dismal prognostic marker.Current work in the field has advanced our understanding of RV myocyte pathobiology significantly in the context of pulmonary vascular disease, particularly with respect to maladaptive molecular mechanisms that modulate RV failure through changes in cellular metabolism, 10 nitric oxide bioavailability, 11,12 and ion channel dysfunction. 13 These basic and translational scientific models, which emphasize novel RV-specific targets to improve RV performance, have illuminated a number of cell-signaling pathways with future therapeutic promise for patients afflicted with pulmonary hypertension-induced RV dysfunction.…”
mentioning
confidence: 99%